Effect of phenolic and alkaloid compounds extracted from Brassica oleracea var. capitata seed on glucose level in blood of alloxan-induced diabetes rabbits - Khalid Abdulkareem Mohammed; Abbas Dawwas Mattar Al-Maliki (World Journal of Experimental Biosciences, 2014)
Brassica oleracea var. capitata is herbal plant traditionally used in different country to treat diabetes. In present study, the chemical compounds of B. oleracea var. capitata seed were specified by GC-Mass technique. Twenty four compounds were found. From these compounds one phenolic compound [2,4- bis(1,1-dimethylethyl)-] and one alkaloid compound (2,3-Dicyano-5,6-diphenylpyrazine) was specified with different concentrations. Alloxan-induced diabetic rabbit was prepared in present study after injecting the experimental rabbit with three doses of alloxan (i.v.). Alloxan-induced diabetic rabbits were divided to two main groups. First group was administrated orally with 0.3 g/kg phenolic compound (test group) while, second group was administrated with 0.3 g/kg alkaloid compounds (test group). The control of both groups was alloxan induced diabetic rabbit administrated orally with normal saline. The lowest level of glucose was observed in alloxan-induced diabetic rabbits that administrated with phenolic compound and the significant reduction was observed after 2 h of administration. While, the moderate reduction of glucose level was observed in alloxan-induced diabetes rabbit that administrated with alkaloid compound and the significant moderate reduction was observed post 24 h. It can be concluded from current study the phenolic compound [2,4-bis(1,1-dimethylethyl)-] that extracted from of B. oleracea var. capitata seed is a good treatment for reducing blood glucose in experimental animal and this compound better is better than alkaloid (2,3-Dicyano-5,6-diphenylpyrazine) in reducing blood glucose.
Keywords: Alkaloid (2,3-Dicyano-5,6-diphenylpyrazine), Alloxan, Diabetic rabbits, Phenol [2,4-bis(1,1- dimethylethyl)-]